Calculation View: multiple-representation editing in spreadsheets - Sarkar, Advait; Gordon, Andy; Peyton Jones, Simon; Toronto, Neil (IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), 2018)
Spreadsheet errors are ubiquitous and costly, an unfortunate combination that is well-reported. A large class of these errors can be attributed to the inability to clearly see the underlying computational structure, as well as poor support for abstraction (encapsulation, re-use, etc). In this paper we propose a novel solution: a multiple-representation spreadsheet containing additional representations that allow abstract operations, without altering the conventional grid representation or its formula syntax. Through a user study, we demonstrate that the use of multiple representations can significantly improve user performance when performing spreadsheet authoring and debugging tasks. We close with a discussion of design implications and outline future directions for this line of inquiry.